Siamese: a case report - Ingar, Jaime (2015)
We present a case of siamese twins diagnosed by ultrasound as thoraco-omphalopagus joint fetuses, at Instituto Nacional Materno Perinatal (Ex Maternidad de Lima). We summarize the clinical history, necropsy protocol and present a short bibliography.